2009
DOI: 10.1007/s00270-009-9592-9
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility, Inflammatory Response, and Recannalization Characteristics of Nonradioactive Resin Microspheres: Histological Findings

Abstract: Intra-arterial radiotherapy with yttrium-90 microspheres (radioembolization) is a therapeutic procedure exclusively applied to the liver that allows the direct delivery of high-dose radiation to liver tumors, by means of endovascular catheters, selectively placed within the tumor vasculature. The aim of the study was to describe the distribution of spheres within the precapillaries, inflammatory response, and recannalization characteristics after embolization with nonradioactive resin microspheres in the kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 25 publications
(24 reference statements)
1
43
0
3
Order By: Relevance
“…We investigated only the latter. An animal study in 9 pigs by Bilbao et al (2) showed that nonradioactive microspheres only induce ulceration when aggregated, and embolization of small distal vessels alone does not cause ulceration. Blood flow was regenerated by the appearance of new vessels or recanalization of occluded vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated only the latter. An animal study in 9 pigs by Bilbao et al (2) showed that nonradioactive microspheres only induce ulceration when aggregated, and embolization of small distal vessels alone does not cause ulceration. Blood flow was regenerated by the appearance of new vessels or recanalization of occluded vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Millions of radioactive microspheres are injected in the hepatic artery to radiate and embolize malignancies (1). Deposition of microspheres in gastrointestinal organs can result in ulceration or inflammation of tissue by a combination of embolization and radiation damage (2)(3)(4). To prevent this, vessels leading to gastrointestinal organs may be coil-embolized in patients scheduled for radioembolization treatment, during a pretreatment session using contrastenhanced images (i.e., digital subtraction angiography complemented by C-arm CT) to identify the culprit vessel (5).…”
mentioning
confidence: 99%
“…The paper by Lewandowski et al also mentions the embolic role of an augmented number of microspheres, although previous results are controversial in this respect: a trend toward improved survival of patients with the stasis phenomenon [29], in contrast to only mild inflammation of animal tissues embolized with nonradioactive resin microspheres [30]. Some caveats should be raised about the new idea.…”
Section: Clinical Importance Of Varying the Number Of Glass Microsphementioning
confidence: 97%
“…This situation is a general indication of extensive intrahepatic tumor growth, extrahepatic spread, progressive functional impairment, and progressive disease and often considered to be a contraindication for TACE (28). However, because RE has no macroembolic effect, it can be applied to patients with portal vein thrombosis (29,30). Al- though the width of portal thrombosis influences the survival time, no significant difference was found in terms of toxicity in the groups with and without portal vein thrombosis (29,31).…”
Section: Portal Vein Thrombosismentioning
confidence: 99%